Immanuel Kant - Höffe, Otfried (State University of New York Press, 1994)
In this book, Hoffe gives a clear, understandable description of Kant's philosophical development and influence, and he sets forth Kant's main ideas from the Critique of Pure Reason and the ethics to the philosophy of law, history, religion, and art. In his critical treatment, Hoffe shows why Kant's philosophy continues to be relevant and challenging to us today.
Keywords: Kant, Immanuel, -- 1724-1804.; Kant, Immanuel, -- 1724-1804; PHILOSOPHY -- History & Surveys -- Modern.